(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2018)
The structural setting and the stratigraphy of the Early to Middle Triassic sedimentary succession exposed in the western part of the Aghdarband window (Kopeh Dag, NE Iran) is described. Six stratigraphic sections in the Sefid-Kuh Limestone, Nazar-Kardeh Formation and Sina Formation have been studied in the tectonic units 1a and 2. The lithostratigraphy is revised, with bio-chronostratigraphic constrain provided by conodonts and ammonoids. The new Olenekian ammonoid genus Megatirolitesis erected. It is based on species thus far known only in Mangyshlak (West Kazakhstan) but it is occurs also in the Sefid-Kuh Limestone.The evolution of the Lower Triassic carbonate ramp of the Sefid-Kuh Limestone, persisted in the Middle Anisian, with a three-stage development (Sefid-Kuh 1, 2 and 3 members) separated by drowning and onset of siliciclastics. The last stage is in part coeval with the Middle Anisian basinal Nazarkardeh Formation.The unconformity-bounded, three-stage development of the carbonate ramp documents that in the Aghdarband Basin the tectonic control over sedimentation started already in the Olenekian, since the onset of the marine transgression. The transgression of the Ladinian Sina Formation sealed a complex morphology resulting from the uplift and erosion of the Middle Anisian units. A new paleogeographic position along the southern Laurasia margin is propsed for the Triassic Aghdarband Basin. Based on the paleobiogeographic affinity of the Olenekian ammonoid occurences, we suggest that the Aghdarband Basin was located in a back-arc position in close connection with Mangyshlak (West Kazakhstan) and Tuarkyr (Turkmenistan), passing northwestward to a large epicontinental basin extending to the Donbass area. At least during the Olenekian the Aghdarband Basin had no direct connection with the Nakhlak Basin, which was proably located in a different intra-arc or more probably fore-arc region with respect to the Palaeotethys subduction-related Triassic arc.